2008
DOI: 10.1080/14622200802163159
|View full text |Cite
|
Sign up to set email alerts
|

Use of flavored cigarettes among older adolescent and adult smokers: United States, 2004-2005

Abstract: Cigarettes with candy, fruit and alcohol flavors have been introduced in recent years as extensions to popular cigarette brands, raising concerns in the public health community that the enticing names, creative packaging, and intense flavorings of these products may be especially appealing to youth. This study used two national surveys to examine the prevalence of use of Camel Exotic Blends, Kool Smooth Fusion, and Salem Silver Label brands during 2004--2005 among older adolescents and young adult smokers aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 8 publications
(12 reference statements)
6
68
0
Order By: Relevance
“…Consistent with evidence that young smokers prefer flavoured cigarettes,7 studies of adolescent and adult smokers find the highest prevalences of menthol cigarette use among 12–17-year-old smokers compared to older smokers and among middle school smokers when compared with high school smokers 5 810. A recent National Survey on Drug Use and Health (NSDUH) report on menthol smoking showed that trends in past month menthol use increased from 13.4% in 2004 to 15.9% in 2010 among people aged 18–25 years old, and remained relatively stable from 2004–2010 among those aged 12–17 years and 26 years and older 11.…”
Section: Introductionsupporting
confidence: 73%
“…Consistent with evidence that young smokers prefer flavoured cigarettes,7 studies of adolescent and adult smokers find the highest prevalences of menthol cigarette use among 12–17-year-old smokers compared to older smokers and among middle school smokers when compared with high school smokers 5 810. A recent National Survey on Drug Use and Health (NSDUH) report on menthol smoking showed that trends in past month menthol use increased from 13.4% in 2004 to 15.9% in 2010 among people aged 18–25 years old, and remained relatively stable from 2004–2010 among those aged 12–17 years and 26 years and older 11.…”
Section: Introductionsupporting
confidence: 73%
“…The prevalence rates for youth smoking discount and native brands of cigarettes in this paper are also very conservative considering we were only able to examine the brand that smokers reported they usually smoke rather than the brand(s) that they may also periodically smoke. This is important as research has previously identified that many smokers consume a wide variety of tobacco products on a periodic basis 22. Owing to limitations with the measures available, we also were unable to determine if the native brands reported by youth smokers were illegal or legal cigarettes manufactured on a First Nations Reserve and/or other brands of cigarettes purchased tax-free on a First Nations Reserve.…”
Section: Discussionmentioning
confidence: 97%
“…[64][65][66] These communities require dedicated resources and more intensive tobacco control efforts. 48,49 Tobacco use initiation and progression to dependence are more common with use of the flavored products. Menthol flavoring is particularly hazardous to children.…”
Section: Tobaccomentioning
confidence: 99%
“…46,47 Flavoring agents increase the appeal of tobacco products to youth. 48,49 The tobacco industry is currently exploiting the looser regulation on noncigarette tobacco products to market fruit-and candy-flavored cigars, small cigars, and electronic nicotine delivery systems. Flavoring agents with local anesthetic properties, such as menthol, decrease the natural sensation of harshness of the tobacco smoke and make it easier to inhale the smoke deeply.…”
Section: Figurementioning
confidence: 99%